Aplicação do ProcesSyNe portuário na avaliação de eficácia da tramitação eletrônica documental para legalização do transporte de cargas no Porto do Rio - Silva, Jeanne Maria Freire (2008)
The purpose and scope of this thesis is to examine the efficacy of the electronic data transfer and document routing system for cargo transport in the port of Rio de Janeiro, introduction of which was accompanied from the outset by this research. The analysis was conducted according to conditions established which correspond to the nationally and internationally standards of Port Information Technology efficacy. The study innovates by applying the Port PROCESSYNE (Port Process System Network) model of network interdependence. This tool, derived from the ProSyNe and ProcesSyNe (Alcântara Gomes models) and developed specifically for this purpose, contributed to the analysis The results of the study offer a way of evaluating Port Information Technology, to meet the expectation that new technologies will come to be added to the system introduced. They also permit planning to contemplate the main procedures, resources and functionalities that will bring greater efficacy to the electronic system analyzed here.